Living arrangements and psychological well-being of the elderly after the economic transition in Vietnam - YAMADA, Ken (Institutional Knowledge at Singapore Management University, 2015)
Objectives: We examine the relationship between living arrangements and psychological well-being of the older adults in Vietnam, where there is an influence of Confucian values and a lack of close substitutes for family care of the older adults, by exploiting a great deal of regional variation in economic development. We also examine the role of living arrangements in well-being differentials across regions. Method: We estimate a triangular simultaneous-equation discrete-response model, which accounts for the simultaneity between living arrangements and psychological well-being (happiness, depression, loneliness, poor appetite, and sleep disorder), using a nationally representative sample of 2,225 adults aged 60 and older drawn from the 2011 Vietnam Aging Survey. Results: Intergenerational coresidence significantly increases the psychological wellbeing of the older adults in Vietnam. The results are fairly robust, even after taking quasicoresidence into account, decomposing the psychological well-being index into each affect and symptom, and splitting the sample by gender. Discussion: Changes in living arrangements induced by differences in labor market opportunities in neighboring regions have resulted in significant differences in psychological well-being among the older adults. The findings point to the need for attention to the mental health of elderly parents left behind in less economically developed regions.